Experimental Investigation of Self-Assembled Particles on Profile Control in the Fuyu Oilfield - Dong, Lifei; Wang, Miao; He, Jie; Ding, Mingchen; Lin, Hun (Frontiers in Chemistry, 2021)
The particle system is one of the widely used profile control agents in many oilfields, and the matching relationship between the particle and the reservoir pore throat is significant for the profile control effect. In order to enhance oil recovery after water breakthrough in the Fuyu oilfield, a self-assembled particle with some branches on the surface, compounded by inverse emulsion polymerization and added, is introduced as the profile control agent in this paper. Then the permeabilities of the water channel and the oil remaining area in the Fuyu oilfield are achieved after the statistic analysis of 1,022 cores from the practical reservoir. Furthermore, the oil restarting pressure in the oil remaining area and the self-assembled particle plugging strength in the water channel are tested. Finally, the adaption of the self-assembled particle and effect of profile control in the Fuyu oilfield are evaluated by comparing the oil restarting pressure and the plugging strength. The results show that the self-assembled particles can be gathered together easily by the force of the ionic bond, which is good for water channel plugging. The permeability of the water channel in the Fuyu oilfield ranges from 1,000 mD to 1,500 mD. The oil restarting pressure increases with the decreasing of permeability, and the increasing rate grows rapidly when it drops below 50 mD. Comparing the oil restarting pressure with the plugging strength, a self-assembled particle with a diameter of 20–40 μm in the water channel with a permeability of 1,265.7 mD can provide sufficient plugging strength to restart the remaining oil in the oil remaining areas with a permeability over 3.38 mD. The matched window of the self-assembled particle is wider than a normal particle in the Fuyu oilfield.